Government livelihood project - free influenza vaccination for the older population in China: the example of Zhejiang Province - Xiaoxiao Wang; Xiaoxiao Wang; Wei Jiang; Zhao Yu; Weiping Jiang; Xiaowei Zhu; Zhen Wang; Jimin Sun; Jimin Sun; Hangjie Zhang; Hangjie Zhang (Frontiers in Public Health)
Influenza vaccination is an effective measure to prevent and control influenza, and countries worldwide consider older people a key recommended population for influenza vaccination. From 2020, Zhejiang Province has provided free influenza vaccination to anyone aged ≥70 years as part of its livelihood projects. In certain counties, the program is also offered to those aged ≥60 years. This measure has made influenza vaccination more convenient and has advanced the strategy for acceptance of influenza vaccines and improved readiness for a pandemic. Furthermore, it serves as an example for other Chinese provinces looking to implement free influenza vaccination programs.